Economic Valuation of Mangrove Forest in Tanakeke Island, Takalar District, South Sulawesi Province - Rini Purwanti (Buletin Eboni, 2020)
Mangrove forests on Tanakeke Island provide many benefits, both direct and indirect benefits. All the benefits received/enjoyed by the community so far have never been calculated/valued in money so sometimes the community does not realize how much value is actually given by this mangrove forest and how much it contributes to their income. Resource economic valuation is a method used to estimate the monetary value of goods and services provided by mangrove forest resources. The purpose of this study was to determine the total economic value of the benefits of mangrove forests on Tanakeke Island. The total economic value of the benefits of mangrove forests is derived from the value of direct benefits (tree, firewood, charcoal, seaweed stake, fish and mangrove crabs), indirect benefits (anchoring abrasion and intrusion), optional benefits, existence benefits and inheritance benefits. Based on the results of calculations, the total economic value of mangrove forests on Tanakeke Island is Rp73,563,108,250.00/year or  Rp127,492,388.00/ha/year. Direct benefits provide the greatest value of Rp44,173,560,000.00/year (60.05%), then indirect benefits of Rp14,257,696,532.00/year (19.38%), the benefit of being Rp10,597,566,668.00/year (14.41%), the inheritance benefit of Rp4,417,356,000/year (6.00%) and optional benefits of Rp116,929,050/year (0.16%).